P76 Psychogenic voice disorder mimicking treatment-refractory respiratory disease. (12th November 2015) - Selby, J; Sandhu, G; Scadding, G; Menzies-Gow, A; Hull, JH
Abstract : Introduction and objectives: Psychogenic voice disorder (PVD) is widely acknowledged by voice and ENT specialists as an important cause of dysphonia and breathlessness. The significance of abnormal vocal function in the aetiology of respiratory symptoms is under-recognised in respiratory medicine. The aim of this study is to highlight the importance of PVD as a key differential diagnosis for patients who present with respiratory symptoms and altered voice quality. Methods: We retrospectively reviewed referrals with respiratory symptoms and dysphonia to the upper airway service at the Royal Brompton, over a 12 month period to 2015. PVD was identified according to accepted criteria: 1 no structural or neurological laryngeal disease, discrepancy between laryngeal status and voice quality, temporary loss of volitional control over phonation, (e.g. frequently reported as secondary to dyspnoea), normal voicing on vegetative manoeuvres (e.g. coughing) and positive psychological factors associated with onset of symptoms. Perceptual voice quality was rated using the GRBAS scale. Results: Ten female patients were identified as having PVD (70% type 2, 20% type 3, 10% type 1). All patients had preserved spirometric indices but daily symptoms of dyspnoea and dysphonia. Respiratory diagnoses at referral included chronic cough (20%), difficult asthma (50%) and unexplained dyspnoea (30%), with symptoms of between 2 months and 15 years' duration. The majority of patients (70%) were receiving treatment with either oral +/- inhaled corticosteroid prior to referral. Perceptual voice quality varied among patients, but in all cases normal voice was restored by the end of the first treatment session, leading to subjective reduction in breathlessness. Relevant psychological factors were identified as an underlying cause of the voice disorder. Conclusion: PVD is an under-recognised cause of treatment-refractory respiratory symptoms in patients with altered voice quality. Prior to referral, these symptoms are often attributed to the use of inhaled corticosteroid, yet accurate diagnosis and targeted therapy permits rapid restoration of normal voice and symptomatic improvement. This case series underpins the importance of collaborative working between SLT and respiratory medicine to ensure patients receive timely and appropriate specialist treatment. Reference: 1 Butcher P, Elias A, Cavalli L. Understanding and treating psychogenic voice disorder: A CBT framework, 2007